Artificial Intelligence Revolutionizing Agriculture: Enhancing Productivity and Sustainability for Global Food Security - Christo, Amos; Mailera, Haruku (IHSA Institute, 2024)
This research investigates the impact of Artificial Intelligence (AI) technology on agricultural productivity, with a focus on its potential to address global food security challenges. Through a comprehensive analysis of AI-driven approaches, including precision agriculture, data-driven decision support systems, crop breeding and genomics, blockchain-enabled supply chain transparency, and robotic agriculture, the research explores the transformative potential of AI in revolutionizing farming practices and enhancing productivity. Key findings highlight the significant implications of widespread adoption of AI technology for farmers, agribusinesses, and policymakers, including increased efficiency, productivity, and competitiveness in the agricultural sector. Moreover, the research underscores the importance of collaboration, investment, and supportive policies to realize the full potential of AI technology in agriculture and promote sustainable and inclusive food systems. This research contributes to the growing body of knowledge on AI technology's role in addressing global food security challenges and provides valuable insights for policymakers, researchers, and stakeholders seeking to harness the transformative power of AI for the benefit of agriculture and society as a whole.